2017
DOI: 10.1111/imj.13523
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of eculizumab in patients with no transfusion history in the International Paroxysmal Nocturnal Haemoglobinuria Registry

Abstract: Significant LDH reduction and clinically meaningful improvement in fatigue were observed in patients with PNH and HDA treated with eculizumab versus untreated patients, irrespective of transfusion history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…In the pivotal phase III clinical trials of eculizumab, a prior history of transfusion was a key study inclusion criterion and transfusion avoidance was one of the benchmarks for evaluating the efficacy of eculizumab 11,12 . In additional studies, eculizumab was associated with significant reduction in intravascular hemolysis and TEs in patients with PNH regardless of their transfusion history 7,13,17 . The current analysis confirms these previous findings and provides additional insights into the impact of eculizumab treatment on transfusion needs in patients with and without bone marrow disease.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the pivotal phase III clinical trials of eculizumab, a prior history of transfusion was a key study inclusion criterion and transfusion avoidance was one of the benchmarks for evaluating the efficacy of eculizumab 11,12 . In additional studies, eculizumab was associated with significant reduction in intravascular hemolysis and TEs in patients with PNH regardless of their transfusion history 7,13,17 . The current analysis confirms these previous findings and provides additional insights into the impact of eculizumab treatment on transfusion needs in patients with and without bone marrow disease.…”
Section: Discussionsupporting
confidence: 74%
“…A more recent analysis of real‐world observational data from patients in the International PNH Registry reported by Almeida et al 13 showed that treatment with eculizumab was associated with significant reductions in intravascular hemolysis in patients who had no history of RBC transfusions. In that study, mean lactate dehydrogenase (LDH) levels decreased from 1674 U/L at baseline to 352 U/L at 6 months in patients treated with eculizumab compared with a minimal decrease (from 1336 U/L at baseline to 1201 U/L) at 6 months in patients who were not treated with eculizumab.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Long-term experience has established that eculizumab is efficacious and well tolerated; however, approximately 11-27% of patients may experience breakthrough hemolysis (BTH) on approved dosages of eculizumab during long-term treatment. [5][6][7] BTH, characterized by the return of intravascular hemolysis and reappearance of classical PNH symptoms, 5,[8][9][10][11] may occur due to suboptimal C5 inhibition, 1 and/or complement-amplifying conditions such as infection, surgery, or pregnancy that may lead to increased complement activation resulting from higher C3b density. [12][13][14] In some patients with suboptimal C5 inhibition or complement-amplifying conditions, BTH may be ameliorated by shortening the 2-week dosing interval and/or increasing the dose of eculizumab.…”
Section: Introductionmentioning
confidence: 99%
“…PNH patients without transfusion history, but with only minor hemolysis- related clinical manifestations, are at risk of early mortality and can now be treated with Eculizumab according to the update of the European approval. 16 Indeed, abdominal pain, the predominant symptom in our patient during the first years of clinical course, is associated with a 3.6-fold greater risk of thrombosis and mortality. 17 Therefore, a new chapter of PNH’s history is opening, on the basis of the new therapeutic indications.…”
Section: Discussionmentioning
confidence: 65%